2011
DOI: 10.1038/ncb2280
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of cohesin rings coordinates the separation of centrioles and chromatids

Abstract: Cohesin pairs sister chromatids by forming a tripartite Scc1-Smc1-Smc3 ring around them. In mitosis, cohesin is removed from chromosome arms by the phosphorylation-dependent prophase pathway. Centromeric cohesin is protected by shugoshin 1 and protein phosphatase 2A (Sgo1-PP2A) and opened only in anaphase by separase-dependent cleavage of Scc1 (refs 4-6). Following chromosome segregation, centrioles loosen their tight orthogonal arrangement, which licenses later centrosome duplication in S phase. Although a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(154 citation statements)
references
References 40 publications
5
145
0
4
Order By: Relevance
“…Inhibition of Plk1 in a Xenopus CSF extract, for example, will block disengagement in the presence of separase (Schockel et al 2011), and overexpression of Plk1 will promote centriole disengagement in G 2 (Loncarek et al 2010). It also seems that APC/C activity contributes to disengagement (Prosser et al 2012), and that Plk1 and APC/ C-Cdh1 activities can independently achieve this (Hatano and Sluder 2012).…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Plk1 in a Xenopus CSF extract, for example, will block disengagement in the presence of separase (Schockel et al 2011), and overexpression of Plk1 will promote centriole disengagement in G 2 (Loncarek et al 2010). It also seems that APC/C activity contributes to disengagement (Prosser et al 2012), and that Plk1 and APC/ C-Cdh1 activities can independently achieve this (Hatano and Sluder 2012).…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
“…Although the notion that centriole disengagement and chromatid separation might share common machinery appears elegant, whether cohesin is a separase substrate in both processes remains confusing. Although one study has reported that a noncleavable cohesin subunit Scc1 would not prevent disengagement in HeLa cells (Tsou et al 2009), another suggested otherwise in Hek293 cells (Schockel et al 2011). If endogenous Scc1 was replaced by a variant carrying a recognition site for human rhinovirus HRV protease or if its partner protein, Smc3, carried a site for TEV protease, these molecules could be cleaved by the appropriate protease resulting in centriole disengagement.…”
Section: The Centrosome and Its Duplication Cyclementioning
confidence: 99%
“…To investigate the effects of genomic instability and resulting aneuploidy on carcinogenesis, various mouse models have been developed, mainly by targeting mitotic or other cell cycle regulators (Foijer, Draviam, & Sorger, 2008; Rao, Yamada, Yao, & Dai, 2009; Ricke, van Ree, & van Deursen, 2008; Schvartzman, Sotillo, & Benezra, 2010). Shugoshin‐1 (Sgo1) protects cohesin proteins and centrosome integrity (Salic, Waters, & Mitchison, 2004; Schöckel, Möckel, Mayer, Boos, & Stemmann, 2011). Cohesins keep sister chromatids from prematurely separating during mitosis, thus ensuring mitotic fidelity (Hirano, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…32 It turns out that separase also mediates timely centriole licensing. 31,[33][34][35] The cell utilizes separase's protease activity to cleave the tight intercentriolar linker to license duplication, thereby coupling centriole duplication mechanistically to the onset of sister-chromatid separation. 34,36 These data engendered the hypothesis that cohesin forms the tight intercentriolar linker.…”
Section: Excess Baggage: How Cancer Cells Acquire Extra Centrosomesmentioning
confidence: 99%